Australian standards of care for cystic fibrosis‐related diabetes. Issue 2 (23rd December 2013) - Middleton, Peter G.; Wagenaar, Monica; Matson, Angela G.; Craig, Maria E.; Holmes‐Walker, Deborah Jane; Katz, Tamarah; Hameed, Shihab
Abstract Multiple guidelines have been published over the last few years for the diagnosis and management of cystic fibrosis (CF) and cystic fibrosis related diabetes (CFRD), although some of the recommendations are based on extrapolation from other forms of diabetes and/or expert opinions. This document seeks to combine the guidelines to provide an Australian approach to the management of CFRD and establish the guidelines within the Australian CF Standards of Care. It is intended that this document will provide assistance to doctors, nurses, dietitians, physiotherapists, diabetes educators and CF patients concerning the issues surrounding CFRD, and will be reviewed and updated in 2016.